The Effect of Cracked Soil on Slope Stability on the Karo Regency Boundary Road – Panji Sta 26+000, North Sumatra Province - Edward Piter Siagian; Indrasurya B. Mochtar; Noor Endah Mochtar; Sriayu Saputri Situmeang (International Journal Labs, 2025)
The landslide incident on the Karo Regency Boundary Road – Panji STA 26+000, North Sumatra Province, showed a decrease in slope stability as indicated by a safety factor (sf) value of less than 1.00. This study aims to analyze the causes of slope instability influenced by the cracked soil phenomenon and heavy rain. The slope stability analysis research method was carried out using Geo5 software based on the limit equilibrium method. The simulation results with the Geo5 application on the original soil conditions showed a safety factor (sf) value of 2.10 which indicated that the slope was in a safe and stable condition. However, after the cracked soil parameters and heavy rain intensity were entered into the Geo5 application, the analysis results showed a drastic decrease in the safety factor (sf) value to 0.93 which indicated that the slope was in an unsafe condition or a landslide. The cracked soil phenomenon increased the infiltration path of rainwater which then accelerated the increase in pore water pressure and weakened the shear strength of the soil, causing landslides.